Assessment of the body posture of children in the school age - Habik-Tatarowska, Natalia (Journal of Education, Health and Sport, 2019)
Nowadays, posture defects are a quite significant medical, economic and social problem. They mainly start when the children start school. It is extremely important to diagnose abnormalities in body posture as soon as possible to implement preventive and curative treatment. The main goal of the study was to assess the posture of children in school age. The research involved a group of 40 children from primary schools in the świętokrzyskie voivodeship. The attitude was assessed using the optoelectronic Diers Formetric III 4D method. It is a photogrammetric video recording via a raster stereography process. The research was carried out in May 2016. The respondents were in the age range 6-13. In 75% of the subjects, the lateral curvature of the spine was observed and in 25% the scoliotic posture was observed. Due to the location of the curvature, the most of them because up to 50% covered the thoracic segment of the spine. Due to the direction, right-sided curves dominated, giving 90%, and due to the number of bends of the curve, the highest number of scoliosis was 80%. In the sagittal plane, the flat back dominated among children, the number of which was 45%. There was no relationship between age and the angle of scoliosis. Studies have shown that the dominant defect in the sagittal plane turned out to be lateral curvature of the spine. The scoliotic attitude mainly concerned boys aged 11 and 12. An important problem turned out to be quite flat backs.